Hygiene, Sanitation, and the Implementation of Hazard Analysis and Critical Control Points (Haccp) in the Nutritional Food Program in Karo Regency - Yuni Marsela Tarigan; Nurmaini Nurmaini; Irnawati Marsaulina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The Free Nutritious Meal Program (MBG) is a government initiative aimed at improving population nutrition by providing safe, nutritious, and high-quality food. Food safety in this program is influenced by sanitation and hygiene conditions as well as the implementation of the Hazard Analysis Critical Control Point (HACCP) system. This study analyzes sanitation and hygiene conditions of facilities and buildings, food sanitation practices, personal hygiene of food handlers, and HACCP implementation at SPPG X and SPPG Y in Karo Regency in 2026. A descriptive observational design was used, with data collected through field observations, interviews, documentation, and checklists based on Permenkes No. 1096 of 2011. HACCP analysis was conducted from raw material receipt to food serving. Results show that SPPG X scored 58 (68.2%), below the minimum standard of 75%, while SPPG Y scored 65 (76%), meeting the standard. Several risks were identified in food processing, storage, and serving stages. Personal hygiene of food handlers was categorized as fairly good (>60%), although discrepancies between observations and questionnaires indicated possible response bias. SPPG X had more critical control points than SPPG Y. Improvements are needed in food processing, temperature control, PPE use, and monthly equipment sanitation. Consistent implementation of hygiene and HACCP principles is essential for ensuring food safety in the MBG program.